1985
DOI: 10.1002/ajmg.1320200107
|View full text |Cite
|
Sign up to set email alerts
|

Kindler syndrome in two related Kurdish families

Abstract: We describe a 19-year-old girl with Kindler syndrome. She has suffered from bullae on pressure areas of the skin since birth. These healed with atrophic scars and caused marked atrophy of the skin of the palms and soles and wrinkled and parchment-like skin of the dorsum of the hands and feet. Since infancy the patient has also suffered from severe photosensitivity on exposed areas and developed poikiloderma on the skin of her face, neck, chest, and upper back. Since age 17 years the patient has been free of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 7 publications
2
44
0
Order By: Relevance
“…9 In 1985, an autosomal recessive pedigree that most closely resembled the original Kindler case was published. 10 Subsequent reports have tended to separate autosomal recessive KS from autosomal dominant Weary syndrome although there has been considerable confusion in establishing distinct clinical entities. Nevertheless, the molecular characterization of some overlapping clinical disorders, such as dystrophic EB caused by pathogenic mutations in the COL7A1 gene, 11 Rothmund-Thomson syndrome caused by mutations in the RECQL4 gene 12 and EB with mottled pigmentation due to mutations in the KRT5 gene 13 has shown that KS is likely to represent a specific genodermatosis.…”
Section: Historical Background Of Kindler Syndromementioning
confidence: 98%
“…9 In 1985, an autosomal recessive pedigree that most closely resembled the original Kindler case was published. 10 Subsequent reports have tended to separate autosomal recessive KS from autosomal dominant Weary syndrome although there has been considerable confusion in establishing distinct clinical entities. Nevertheless, the molecular characterization of some overlapping clinical disorders, such as dystrophic EB caused by pathogenic mutations in the COL7A1 gene, 11 Rothmund-Thomson syndrome caused by mutations in the RECQL4 gene 12 and EB with mottled pigmentation due to mutations in the KRT5 gene 13 has shown that KS is likely to represent a specific genodermatosis.…”
Section: Historical Background Of Kindler Syndromementioning
confidence: 98%
“…Only few case reports of patients with Kindler syndrome describe their oral features 34,[85][86][87][88][89][90] . The evidence suggests that patients with Kindler syndrome can present with fragile mucosa, microstomia, and partial vestibule obliteration, although microstomia was not identified in all patients with Kindler syndrome 34,85,86 .…”
Section: Kindler Syndromementioning
confidence: 99%
“…Several other features have been reported which vary between cases including: digital webbing; palmoplantar keratoderma; nail dystrophy; alopecia; oesophageal, anal, vaginal and urethral stenosis; loss of dermatoglyphics; and phimosis [1,3,[5][6][7]. A wide range of oral manifestations of the syndrome have also been described including mucosal white patches, atrophy and blistering; gingival bleeding and severe periodontitis; ankyloglossia; restricted mouth opening; and malocclusion [1,2,[6][7][8][9].…”
Section: Introduction and Clinical Featuresmentioning
confidence: 97%
“…features of two previously described conditions, epidermolysis bullosa hereditaria and poikiloderma congenitale. The characteristic clinical features are acral blistering and photosensitivity in infancy followed by progressive poikiloderma (diffuse cutaneous atrophy, telangiectases and reticulate pigmentation) later in life [1,2]. Blistering may be spontaneous or traumatic and usually resolves with age, although there is one reported case where bullae recurred in the fifth decade [3].…”
Section: Introduction and Clinical Featuresmentioning
confidence: 97%